2020
DOI: 10.1016/j.arcped.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge assessment of sudden infant death syndrome risk factors in expectant mothers: A prospective monocentric descriptive study

Abstract: In France, approximately 500 deaths per year are related to sudden infant death syndrome (SIDS). After a 75% reduction of SIDS-related deaths in the 1990s, thanks to large prevention campaigns directing parents to put their infants to sleep on their back, the number of SIDSrelated deaths remains stable. However we estimate that 100 to 200 deaths of infants per year in France could be preventable with a better education to the risk factors of SIDS.In this prospective and descriptive monocentric study, we aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
2
11
1
1
Order By: Relevance
“…This knowledge gap among Saudis highlights the importance of implementing educational interventions and campaigns to improve public awareness regarding the correct sleeping practices and avoiding other SIDS risk factors. The majority of our participating mothers reported that media platforms (social media and websites) were the main source of information from where they heard about SIDS, which was found to be similar to other previous studies done in France and Turkey [2,13]. This study suggests that families might be informed effectively about SIDS by way of the media.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This knowledge gap among Saudis highlights the importance of implementing educational interventions and campaigns to improve public awareness regarding the correct sleeping practices and avoiding other SIDS risk factors. The majority of our participating mothers reported that media platforms (social media and websites) were the main source of information from where they heard about SIDS, which was found to be similar to other previous studies done in France and Turkey [2,13]. This study suggests that families might be informed effectively about SIDS by way of the media.…”
Section: Discussionsupporting
confidence: 86%
“…The awareness of SIDS among non-Saudi mothers was higher than Saudi mothers (60.7%% vs 46.3%). In France, a study on 202 pregnant women displayed 94.6% of women stated that they had heard about SIDS before [13]. This percentage of awareness is almost double the percentage of Saudi mothers who have heard about SIDS in our report.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Many soft bedding items are marketed to reduce plagiocephaly, which is stated by 21%-29% of parents as a reason for non-adherence to infant sleeping guidelines. 31,32 Intention to use a soother was decreased in mothers intending to Validated information is available online, and safe sleep information is provided by all maternity hospitals to parents prior to discharge. 12,35 Recently published national standards should improve the quality of antenatal education.…”
Section: Discussionmentioning
confidence: 99%
“…Universidade Vila Velha (UVV), Vila Velha -ES 7. Universidade de Ribeirão Preto (UNAERP), Guarujá -SP 8. Centro Universitário de Caratinga (UNEC), Caratinga -MG.…”
unclassified